CIVIL LAW ASPECTS OF INFRINGEMENT ON TWO-DIMENSIONAL ART COPYRIGHT WORKS MADE INTO NON-FUNGIBLE TOKENS (NFT) - Ngaisah, Siti; Keni, Grefitha Yasanova (YURIS: Journal of Court and Justice, 2024)
NFTs, or Non-Fungible Tokens, are digital assets referring to objects, such as art, music, in-game items, videos, and any other type of work represented in digital form. Two-dimensional artworks, including paintings, drawings, and sculptures, gain legal protection as copyrighted works. The use of NFTs is identified as a potential tool in preventing copyright infringement, verifying authenticity, and providing legal certainty for owners and buyers of digital artworks. This research aims to identify the regulation and protection of copyright for two-dimensional artworks in the context of the use of Non-Fungible Tokens (NFTs) under Law No. 28/2014 on Copyright (UUHC). Through normative research with a statutory approach, this research aims to examine the regulation of copyright infringement of two-dimensional artworks embodied in NFTs and comprehend the legal aspects related to their infringement. The research findings indicate that, although NFTs offer a mechanism to strengthen proof of ownership and authenticity, there remains a lack of effective legal and policy frameworks to protect copyright and support the growth of the digital art industry. The findings underscore the importance of concerted efforts in strengthening copyright protection in the digital age and raising public awareness on the significance of respecting and abiding by copyrighted artworks.